Hydrogen detection properties of palladium sputtered polyacrylonitrile nanofibrous layers. (4th January 2021) - Ahmadi, Mahsa; Tavanai, Hossein; Ranjbar, Mehdi; Goodarzi, Mehdi Torabi
Abstract: In this research, electrospun polyacrylonitrile (PAN) nanofibrous layers are investigated as substrate for palladium‐based resistive type hydrogen sensors. The fabricated sensors showed sensitivity to hydrogen with a concentration as low as 12 ppm at room temperature. Up to 50 ppm hydrogen concentration, hydrogen induced lattice expansion (HILE) constituted the mechanism, whereas, with concentrations of 125 ppm and higher, palladium hydride formation (PdHx ) mechanism ruled. For equal palladium thickness, the response of the sensors increased with increasing nanofiber diameter. With constant diameter of nanofibers, response and response time increased with thicker palladium layer. The sensor with 104 nm nanofibers and 4 nm palladium layer showed the best behavior. The sensor with nanofibrous substrate showed a higher response and lower response time in comparison to glass, PAN film, and PAN fibrous (fiber diameter: 16 μm, non‐nanofiber) substrate.